Transfer of know-how for small and mid-size businesses in Georgia, Moldova and Ukraine. White Paper: Ukraine - Erik Kubicka; Andrej Piovarci; Jozef Simuth; Vladimir Dubrovskiy (Center for Social and Economic Research (CASE), 2015)
This project aims to assist SMEs in Georgia, Moldova and Ukraine by providing support to stakeholders in their efforts to develop analytical and policy advocacy capabilities and by opening new channels of communication between SMEs and NGOs in the Visegrad Four countries (Czech Republic, Hungary, Poland and Slovakia) and the rest of the European Union. The aim is to facilitate the transfer of knowledge and to establish a permanent platform for sustainable cooperation that will bring SMEs in the beneficiary countries closer to EU standards, markets, and business opportunities.1 The objective of this document is to deliver the complete findings and outcomes of the project aimed at Ukraine. This White Paper serves as an authoritative document with action plans, budgets, and a tangible way for the beneficiary country stakeholders to move forward with the agenda of small and medium-sized business development. [...]
Keywords: H25; O12; L26; O11; O19; 330; small and middle enterprises (SMEs); know-how; knowledge transfer; European Union; Visegrad Group; Eastern Partnership